Early MRI Detection and Closed Bone Graft Epiphysiodesis May Alter the Course of Avascular Necrosis Following Unstable Slipped Capital Femoral Epiphysis. Issue 4 (April 2018) - Napora, Joshua K.; Gilmore, Allison; Son-Hing, Jochen P.; Grimberg, Dominic C.; Thompson, George H.; Liu, Raymond W.
Abstract : Background: Unstable slipped capital femoral epiphysis (SCFE) has an increased incidence of avascular necrosis (AVN). Early identification and surgical intervention for AVN may help preserve the femoral head. Methods: We retrospectively reviewed 48 patients (50 hips) with unstable SCFE managed between 2000 and 2014. AVN was diagnosed based on 2 different postoperative protocols. Seventeen patients (17 hips) had a scheduled magnetic resonance imaging (MRI) between 1 and 6 months from initial surgery, and the remaining 31 patients (33 hips) were evaluated by plain radiographs alone. If AVN was diagnosed, we offered core decompression and closed bone graft epiphysiodesis (CBGE) to mitigate its affects. At final follow-up, we assessed progression of AVN using the Steinberg classification. Results: Overall 13 hips (26%) with unstable SCFEs developed AVN. MRI revealed AVN in 7 of 17 hips (41%) at a mean of 2.5 months postoperatively (range, 1.0 to 5.2 mo). Six hips diagnosed by MRI received surgical intervention (4 CBGE, 1 free vascularized fibula graft, and 1 repinning due to screw cutout) at a mean of 4.1 months (range, 1.3 to 7.2 mo) postoperatively. None of the 4 patients treated with CBGE within 2 months postoperatively progressed to stage IVC AVN. The 2 patients treated after 4 months postoperatively both progressed to stage VC AVN. Plain radiographs demonstrated AVN in 6 of 33 hips (18%) at a mean of 6.8 months postoperatively (range, 2.1 to 21.1 mo). One patient diagnosed with stage IVB AVN at 2.4 months had screw cutout and received CBGE at 2.5 months from initial pinning. The remaining 5 were not offered surgical intervention. Five of the 6 radiographically diagnosed AVN, including the 1 treated with CBGE, progressed to stage IVC AVN or greater. Conclusions: Although all patients with positive MRI scans developed radiographic AVN, none of the 4 patients treated with CBGE within 2 months after pinning developed grade IVC or greater AVN. Early MRI detection and CBGE may mitigate the effects of AVN after SCFE. Level of Evidence: Level III—retrospective comparative study.